THE INFLUENCE OF CREATIVITY AND LEARNING MOTIVATION ON STUDENTS' LEARNING INDEPENDENCE WITH FRIEND SUPPORT AS MODERATING VARIABLES - Wulanningtyas, Nova Dyah; Fauzan, Fauzan (IJOSMAS, 2022)
The purpose of this study was to determine the effect of creativity on student learning independence at SMK Negeri 3 Kendal. Knowing the effect of learning motivation on student learning independence at SMK Negeri 3 Kendal. Knowing the effect of creativity on student learning independence at SMK Negeri 3 Kendal moderated by the support of friends. Knowing the effect of learning motivation on student learning independence at SMK Negeri 3 Kendal moderated by the support of friends. This study uses quantitative methods with a total sample of 100 out of 134 existing populations. Research data obtained by observation, interviews and documentation studies. It was concluded that creativity had a positive and significant effect on learning independence. Learning motivation has a positive and significant effect on learning independence. Support from friends moderates the effect of creativity on student learning independence. Support from friends moderates the effect of learning motivation on student learning independence.